A study on the preparation of chitosan-tripolyphosphate nanoparticles and its entrapment mechanism for egg white derived peptides. (15th July 2019) - Du, Zhiyang; Liu, Jingbo; Zhang, Ting; Yu, Yiding; Zhang, Yan; Zhai, Jinxing; Huang, Haitao; Wei, Shibiao; Ding, Long; Liu, Boqun
Highlights: The size, PDI and ζ-potential of chitosan nanoparticle are controllable. Peptide molecular weight affected the size and ζ-potential of chitosan nanoparticle. Peptide molecular weight affected the entrapment efficiency of chitosan nanoparticle. The findings are important in designing chitosan nanoparticle delivering peptide. Abstract: The entrapment of peptides can effectively improve their bioavailability and commercial application. This research sought to investigate the mechanism of entrapment of egg white derived peptides (EWDP) loaded in chitosan-tripolyphosphate (CS-TPP) nanoparticles (NPs). It was shown that CS molecular weight (MW), pH, CS-TPP mass ratio and CS concentration can all affect the size, polydispersity index and zeta potential of CS-TPP NPs. Moreover, these factors, as well as different MW and CS mass ratio of peptides also had an influence on entrapment efficiency (EE). Furthermore, peptides influenced the zeta potential after they were loaded in the CS-TPP NPs. This suggested that the peptide charged groups were in different locations relative to the CS-TPP NPs surfaces. FTIR analysis indicated that the peptides interacted with CS-TPP NPs through strong hydrogen bonds and electrostatic interactions. These findings are important for designing delivery systems used for commercial production of entrapped peptides with enhanced attributes.